1999
DOI: 10.4141/a98-096
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of reproductive and growth traits of horned and polled cattle in three synthetic beef lines

Abstract: Goonewardene, L. A., Pang, H., Berg, R. T. and Price, M. A. 1999. A comparison of reproductive and growth traits of horned and polled cattle in three synthetic beef lines. Can. J. Anim. Sci. 79: 123-127. The data for the study were obtained over an 11-yr period and the number of observations varied from 2663 to 4263 depending on the trait that was studied. The objective was to compare the reproduction and growth traits of genetically horned and polled cattle in three synthetic lines of beef cattle. No differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…The DS had higher (P < 0.01) weaning weights and preweaning gains compared with BS1 and BS2 due to the influence of the dairy genetics in the composite. The breed group differences recognized in this study are similar to previous reports by Pang et al (1998) and Goonewardene et al (1999). Marbling was lower (P < 0.01) in BS2 compared with BS1 and DS, while BS1 had a higher (P < 0.01) REA and cutability compared with BS2 and DS.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…The DS had higher (P < 0.01) weaning weights and preweaning gains compared with BS1 and BS2 due to the influence of the dairy genetics in the composite. The breed group differences recognized in this study are similar to previous reports by Pang et al (1998) and Goonewardene et al (1999). Marbling was lower (P < 0.01) in BS2 compared with BS1 and DS, while BS1 had a higher (P < 0.01) REA and cutability compared with BS2 and DS.…”
supporting
confidence: 90%
“…The phenotypic similarities, however, in traits associated with reproduction, fitness, growth and carcass need to be established between horned and polled cattle before breeding for polledness can be recommended. In earlier studies we showed that horned and polled cattle were similar for growth and reproductive traits (Stookey and Goonewardene 1996;Goonewardene et al 1999), but little information is available on carcass traits. The objective of this study was to compare the growth and carcass traits of genetically horned and polled beef bulls from three composite (synthetic) breed groups.…”
mentioning
confidence: 97%
See 3 more Smart Citations